Pengembangan media video animasi berbasis audio visual powtoon pada materi siklus air - M. Hadi Satria; Hadi Soekamto; Alfi Sahrina; Dwiyono Hari Utomo (Universitas Negeri Malang, 2023)
This research is motivated by students' needs for animated video media as a support for complex and abstract water cycle material that is difficult for students to understand. This study aims to produce media in the form of animated videos that have superior components in the form of additional material,